2022
DOI: 10.1136/bmjopen-2021-056411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of local handwashing agents on microbial contamination of the hands in a rural setting in Northwest Ethiopia: a cluster randomised controlled trial

Abstract: ObjectiveTo evaluate the effectiveness of handwashing with water and wood ash in reducing faecal contamination of the hands.DesignA cluster randomised controlled trial was employed with two arms: handwashing with water and wood ash versus handwashing with water alone.SettingRural households of East Dembiya District, Central Gondar Zone, Amhara National Regional State, Ethiopia.Participants440 mothers and caregivers of children younger than 5 years assigned (1:1, 220 in each group) in clusters, with buffer zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In general, the microbiota of restroom environments is intimately linked to the human microbiome. Different feeding patterns, hands, and skin lead to the establishment of microbial profiles, which also were described in other studies (25,26,27). The idea to define the bacterial biotope was already explored (28), especially in restrooms (7,29).…”
Section: Discussion (1242 Words)mentioning
confidence: 76%
“…In general, the microbiota of restroom environments is intimately linked to the human microbiome. Different feeding patterns, hands, and skin lead to the establishment of microbial profiles, which also were described in other studies (25,26,27). The idea to define the bacterial biotope was already explored (28), especially in restrooms (7,29).…”
Section: Discussion (1242 Words)mentioning
confidence: 76%
“…This finding could be explained by the fact that in areas where human and animal excreta are disposed in an unhygienic way, hands are more contaminated. It is typically the case of rural area where animal husbandry within the household environment is common and exposure to human and animal faeces is of particular concern [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between bacteria, skin cells and immune cells can repair and reinforce the barrier formed by the skin and the disruption of this interaction can leave the skin susceptible to eczema and skin allergies, or interfere with the healing of people with diabetic ulcers [ 14 ]. A causal link exists between hand hygiene and infection transmission [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…De Alwis and colleagues revealed that contaminated surfaces such as toilets and washrooms could be the sources of contamination of the hands when a person comes into contact [ 36 ]. In addition, the microbial contamination of hands could be due to the ineffectiveness of handwashing agents [ 40 ]. Moreover, ignorance of handwashing with soap, touching dirty materials, and long fingernails [ 12 , 41 ].…”
Section: Discussionmentioning
confidence: 99%